Energy-efficient Constrained Control of a Hydrostatic Power Split Drive. Issue 1 (July 2017) - Zeman, P.; Kemmetmüller, W.; Kugi, A.
Abstract: Although hydrostatic transmissions achieve lower efficiencies compared to mechanical gears with a fixed transmission ratio, the efficiency of the overall drive train can be increased by operating the internal combustion engine (ICE) in an energetically optimal set point. The overall efficiency can be further increased by using power split drives, where the power is transmitted across a hydraulic and a mechanical path. In this paper, a torque control strategy for an output-coupled power split drive of a hybrid hydraulic vehicle (HHV) is developed. A steady-state minimization of the power loss yields the basis for a multi-input multi-output (MIMO) closed-loop control concept of the ICE speed and the hydraulic pressure. A tailored feed-forward controller systematically accounts for the input constraints of the system. A feedback controller compensates for parameter uncertainties and un-modeled disturbances. Simulation studies of a nonlinear model of the drive train prove the feasibility and the robustness of the proposed control approach.